Politics of the modern form - Agostinho, Larissa Drigo [UNESP] (Univ Fed Minas Gerais, Fac Letras, 2024)
Since romanticism is fundamental to Antonio C & acirc;ndido's work, especially his Forma & ccedil;& atilde;o da literatura brasileira, we try in this article, based on Baudelaire and Mallarm & eacute;, to relocate some of the problems posed by romanticism and perhaps define a post-romanticism that would allow us to rethink the political function of form, especially in poetry. We will start with the exemplary way in which Mallarm & eacute;'s reception raised the problems of the relation between form and politics, and then define Baudelaire's lyricism and the place his poetry occupies in the symbolic destruction of the cultural basis of romanticism. Baudelaire's opposition between classic and modern can lead us to redraw the importance ofthe irruption ofthe horrible life or prose or the intensity of life in his poetry in order to rewrite another history of lyricism.
Keywords: lyricism; romanticism; modernity; structuralism; Marxism